(untitled) (Research, Society and Development, 2022)
Objective: To investigate the mental health risks of the vaccination campaign against COVID-19 of licensed practical nurses at primary health care in a region of São Paulo. Methods: The research had two stages, in the first, there was a documentary analysis of procedures and guidelines for vaccination against COVID-19, and free observations with field diary records. In the second, there was the selection of licensed practical nurses, to obtain personal and work data, and conducting individual semi-structured interviews for thematic content analysis. Results: Participated in this study five licensed practical nurses aged between 26 and 54 years old, and most of them were female. In the analysis, it was found an accelerated place of work, repetitiveness, excess of information, lack of training, fear of contamination, experiences of threats, verbal aggression, and distrust on the part of users, among others, with dimensioned team and impacts on health and life. Conclusion: Various situations were identified as risk for mental health of licensed practical nurses during the vaccination campaign. There is a need for better working conditions and modes of working organization during vaccination in pandemics situations.